SYNTHESIS AND PROPERTIES OF A BIOCOMPOSITE HYDROGEL BASED ON CARBOXYMETHYL CELLULOSE AND SERICIN (Scientific journal of the Fergana State University, 2026)
In this article, a biocomposite hydrogel was synthesized based on purified sodium carboxymethyl cellulose (Na-CMC) with a degree of substitution (DS)  0.88 and a degree of polymerization (DP) 850, together with sericin obtained from natural silk. The physicochemical properties of the resulting hydrogel were analyzed. Electrostatic interactions between the carboxyl (–COO⁻) groups of Na-CMC and the amide-I and amide-II groups of sericin macromolecules were identified in the IR-Fure spectrogram                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                     within the range of 1600–1700 cm⁻¹. Rheological studies confirmed that intermolecular cross-linking between the functional groups of Na-CMC and sericin led to a proportional increase in the viscosity of the hydrogel. After lyophilization of the Na-CMC/sericin hydrogel, scanning electron microscopy (SEM) revealed a porous structure with pore sizes in the range of 20-110 μm.